An Inventory of International Student Services at 200 U.S. Universities and Colleges: Descriptive Data of Pre-Departure and Post-Arrival Supports - Madden-Dent, Tara; Wood, Dawn; Roskina, Katerina (Journal of International Students, 2019)
During the spring semester of 2018, a survey of international student support services was conducted on 200 randomly selected U.S. universities and colleges using the International Student Support Services Index. Survey results identified the most and least commonly provided international student support services in addition to common patterns of institutional practices around international student support across the US. The research results are complemented by researcher notes and observations in addition to school administrator quotes. This article concludes with recommendations and implications for practice. Colleges and universities wanting to recruit and retain culturally and academically prepared international students may benefit from learning how other institutions offer integration support services.